Clinical Experience of Using Cortical Auditory Evoked Potentials in the Treatment of Infant Hearing Loss in Australia - Punch, Simone; Van Dun, Bram; King, Alison; Carter, Lyndal; Pearce, Wendy (Seminars in Hearing, 2016)
This article presents the clinical protocol that is currently being used within Australian Hearing for infant hearing aid evaluation using cortical auditory evoked potentials (CAEPs). CAEP testing is performed in the free field at two stimulus levels (65 dB sound pressure level [SPL], followed by 55 or 75 dB SPL) using three brief frequency-distinct speech sounds /m/, /ɡ/, and /t/, within a standard audiological appointment of up to 90 minutes. CAEP results are used to check or guide modifications of hearing aid fittings or to confirm unaided hearing capability. A retrospective review of 83 client files evaluated whether clinical practice aligned with the clinical protocol. It showed that most children could be assessed as part of their initial fitting program when they were identified as a priority for CAEP testing. Aided CAEPs were most commonly assessed within 8 weeks of the fitting. A survey of 32 pediatric audiologists provided information about their perception of cortical testing at Australian Hearing. The results indicated that clinical CAEP testing influenced audiologists' approach to rehabilitation and was well received by parents and that they were satisfied with the technique. Three case studies were selected to illustrate how CAEP testing can be used in a clinical environment. Overall, CAEP testing has been effectively integrated into the infant fitting program.
Keywords: Cortical auditory evoked potential; hearing; hearing aid; infant